PELATIHAN MENGENALI DIRI DAN ORANG LAIN UNTUK MENINGKATKAN KINERJA SDM UMKM CILODONG BERKARYA DEPOK - Winnie Septiani; Triwulandari Satitidjati Dwiyana; Rahmi Maulidya (Universitas Trisakti, 2023)
UMKM is a part of the national economy with the potential and independence to improve the community's economy. In enhancing its performance, UMKM Cilodong Berkarya (Ciber) Depok City faces various obstacles, including the version of its human resources. HR performance in the organization is also determined by the ability of all elements to synergize with all the potential within the organization. This training aims to provide knowledge and understanding of several approaches that can be used to identify oneself and others. The training was attended by 30 participants, most of whom have businesses in the culinary field with an average length of business of 2–3 years. The material given in this training is about the importance of getting to know ourselves and others, some core approaches to self, filling in personality plus, how to read the results, and how to recognize other people quickly. The systems and methods given to get to know yourself include the Johari Window, the Enneagram, DISC (Dominance, Influence, Steadiness, and Compliance), and Personality Plus (Choleric, Melancholy, Sanguine, and Phlegmatic). From this training, participants are expected to recognize their strengths and weaknesses to become personable, productive, fun for others, and able to build effective communication. The training evaluation results showed that 90% were satisfied with the training materials provided and that they provided benefits for the participants. 90% of the participants stated that they were interested in participating in the next training.